Trig........
posted by abdo .
I need to prove that the following is true. Thanks
(cosx / 1sinx ) = ( 1+sinx / cosx )
I recall this question causing all kinds of problems when I was still teaching.
it requires a little "trick"
L.S.
=cosx/(1sinx) multiply top and bottom by 1+sinx, (creating the difference of square pattern)
=cosx(1+sinx)/[(1sinx)(1+sinx)]
=cosx(1+sinx)/(1sin^2x)
=cosx(1+sinx)/cos^2x divide by cosx
= (1+sinx)/cosx
= R.S.
Wow !!
Respond to this Question
Similar Questions

Math
Verify the identity . (cscXcotX)^2=1cosX/1+cosX _______ sorry i cant help you (cscXcotX)=1/sinX  cosX/sinX = (1cosX)/sinX If you square this you have (1cosX)^2/(sinX)^2 Now use (sinX)^2 = 1  (cosX)^2 to get (1cosX)^2 / 1  … 
PreCalc
Trigonometric Identities Prove: (tanx + secx 1)/(tanx  secx + 1)= tanx + secx My work so far: (sinx/cosx + 1/cosx + cosx/cosx)/(sinx/cos x  1/cosx + cosx/cosx)= tanx + cosx (just working on the left side) ((sinx + 1  cosx)/cosx)/((sinx … 
Trigonometry.
( tanx/1cotx )+ (cotx/1tanx)= (1+secxcscx) Good one! Generally these are done by changing everything to sines and cosines, unless you see some obvious identities. Also generally, it is best to start with the more complicated side … 
Precalc
prove the identity: (cosx)(tanx + sinx cotx)=sinx+cos(squared)x i need steps to show how i got the answer generally, it is a good idea to change all trig ratios to sines and cosines, and start with the more complicatedlooking side. … 
Mathematics  Trigonometric Identities
Prove: (tanx)(sinx) / (tanx) + (sinx) = (tanx)  (sinx) / (tanx)(sinx) What I have so far: L.S. = (sinx / cosx) sinx / (sinx / cosx) + sinx = (sin^2x / cosx) / (sinx + (sinx) (cosx) / cosx) = (sin^2x / cosx) / (cosx / sinx + sinxcosx) 
Math  Pre Clac
Prove that each of these equations is an identity. A) (1 + sinx + cos x)/(1 + sinx + cosx)=(1 + cosx)/sinx B) (1 + sinx + cosx)/(1  sinx + cosx)= (1 + sin x)/cosx Please and thankyou! 
Trigonometry Check
Simplify #3: [cosxsin(90x)sinx]/[cosxcos(180x)tanx] = [cosx(sin90cosxcos90sinx)sinx]/[cosx(cos180cosx+sinx180sinx)tanx] = [cosx((1)cosx(0)sinx)sinx]/[cosx((1)cosx+(0)sinx)tanx] = [cosxcosxsinx]/[cosx+cosxtanx] = [cosx(1sinx]/[cosx(1+tanx] … 
trigonometry
can i use factoring to simplify this trig identity? 
Precalculus/Trig
Prove the following identity: 1/tanx + tanx = 1/sinxcosx I can't seem to prove it. This is my work, I must've made a mistake somewhere: Converted 1/tanx: 1/sinx/cosx + sinx/cosx = 1/sinxcosx Simplified 1/sinx/cosx: cosx/sinx + sinx/cosx … 
Precalculus/Trig
I can't seem to prove these trig identities and would really appreciate help: 1. cosx + 1/sin^3x = cscx/1  cosx I changed the 1: cosx/sin^3x + sin^3x/sin^3x = cscx/1cosx Simplified: cosx + sin^3x/sin^3x = cscx/1cosx I don't know …